Penerapan Fatwa Dewan Syariah Nasional No. 29/DSN-MUI/VI/2002 Tentang Pembiayaan Pengurusan Haji di BMT Surya Madani Boyolali - Nasrudin, Muhammad, Dr. Imron Rosyadi, M.Ag (2017)
Baitul Māl wat-Tamwil (BMT) is one of the non-Bank Syariah Financial Institutions (LKS) which mostly have hajj financing products. This Hajj financing has been regulated in the DSN-MUI fatwa no. 29 / DSN-MUI / VI / 2002 which states that the hajj financing is done by al-Qardh contract, which in it is not something profitable but only a pure loan. The purpose of this research is to know the implementation of fatwa DSN-MUI. 29 / DSN-MUI / VI / 2002 on hajj financing products in BMT Surya Madani Boyolali. This research uses field research type with qualitative descriptive approach. Data obtained from interviews, documentation, and observation with BMT Surya Madani. Then the data is analyzed using descriptive analysis method by linking data with theory. The result of the research shows that BMT Surya Madani in running hajj financing product is different from that which has been stated by fatwa of National Sharia Council MUI. Fatwa Dewan Syariah Nasional No. 29 / DSN-MUI / VI / 2002 mentioned that in haj financing using al-qardh contract but BMT Surya Madani use Ijārah and rahn contract in lieu of qardh contract.